Neurological Complications of Biological Treatment of Psoriasis - Mateusz Kamil Ożóg; Beniamin Oskar Grabarek; Magdalena Wierzbik-Strońska; Magdalena Świder (Life, 2022)
In the available literature, little attention has been paid to the assessment of psoriasis and the biological therapy used for it and the nervous system. The purpose of this article is to discuss the relationship between psoriasis and the nervous system as well as to analyze the mechanisms that lead to neurological complications during anticytokine therapies in psoriasis. However, this connection requires further analysis. The use of biological drugs in psoriasis, although it yields positive therapeutic results, is not without numerous side effects. Serious neurological side effects of the therapy are most often visible with the use of anti-TNF-alpha, which is why patients should be monitored for their potential occurrence. Early detection of complications and rapid discontinuation of treatment with the drug may potentially increase the patient’s chances of a full recovery or improvement of his/her neurological condition. It also seems reasonable that, in the case of complications occurring during anti-TNF-alpha therapy, some of the drugs from other groups should be included in the therapy.